The roles of Klotho and FGF-23 in bipolar manic episode - Emir, B. Sirlier; Yildiz, S.; Kilicaslan, A. Kazgan; Kilic, F.; Ugur, K.; Aydin, S.; Atmaca, M. (Verduci Publisher, 2023)
OBJECTIVE: Bipolar disorder (manic episode) is an essential psychiatric disorder with unknown etiology, in which inflammation is considered to play a role. Klotho and FGF-23 are known to be associated with inflammation. Therefore, this study aimed to determine the link between Klotho and FGF-23 levels and bipolar disorder. PATIENTS AND METHODS: In this study, 42 men with BD and 41 healthy controls were enrolled, followed up, and/or treated at the High-Security Forensic Psychiatry Clinic. Sociodemographic data form, Young Mania Rating Scale, and Hamilton Depression Rating Scale were applied to all participants. RESULTS: Klotho and FGF-23 levels were significantly increased in patients with BD manic episodes. There was no correlation between Klotho and FGF-23 levels and clinical parameters. For Klotho and FGF-23, cutoff values of 69 and 1,646 yielded 67.4% sensitivity and 72.1% specificity and 81.4% sensitivity and 51.2% specificity, respectively. CONCLUSIONS: Klotho and FGF-23 may play critical roles in the etiopathology of manic episodes and are potential candidate biomarkers for bipolar disorder. This relationship might contribute to the etiopathogenesis of the disease and determine its treatment. Anti-Klotho and anti-FGF-23 administration may be a future treatment for controlling the course of the disease.
Keywords: Bipolar disorder; Inflammation; Klotho; FGF-23